Angular Cuts for Expansion Paths in Transmis-sion System Planning - Laura Mónica Escobar, V. [UNESP]; Romero L, Rub?n A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
this paper presents a methodology to solve the long-Term transmission expansion planning problem incorporating angular cuts based in the constraints impose for expansion circuits with low capacity-reactance product over other circuits with high capacity-reactance product in parallel with them. These cuts aim to reduce the search space of the problem and the total time of compute of this NP-hard problem. To construct these angular cuts the method uses information of the power flows obtained in the system when it is solved using the continuous model, the transport model and the hybrid model. The problem considers high voltage alternating current (HVAC) investment options in lines and substations. A traditional southern Brazilian of 46 nodes test system is used to show the efficiency of the proposed approach. The tests are performed solving the transmission planning problem using the reduced disjunctive DC model for cases with and without angular cuts.
Keywords: Angular cuts; Disjunctive model; long-Term; optimization; transmission expansion planning